Evaluation of drive technology for a dry gravity energy storage system - Mugyema, Morris (Stellenbosch : Stellenbosch University, 2025)
Mugyema, M. 2025. Evaluation of Drive Technology for a Dry Gravity Energy Storage System. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/0443c012-2ab6-4b79-a26d-46c4a3945467